2017
DOI: 10.1242/dmm.030767
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical NF-κB signaling and the essential kinase NIK modulate crucial features associated with eosinophilic esophagitis pathogenesis

Abstract: Eosinophilic esophagitis (EoE) is an allergic disease of the esophagus driven by T cell and eosinophil responses to dietary allergens, resulting in chronic mucosal inflammation. Few spontaneous animal models of esophageal eosinophilia exist, with most studies relying on artificial sensitization procedures. NF-κB-inducing kinase (NIK; MAP3K14) is a key signaling molecule of the noncanonical NF-κB (NFKB1) pathway, an alternative signaling cascade producing chemokines involved in lymphoid stroma development and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…To better define the mechanisms underlying the in vivo response to Magnéli phase exposure, lung tissue was collected 7 days post-exposure. Total RNA was isolated and processed for gene expression profiling using the SuperArray platform and IPA, as previously described (79). The gene expression profiling analysis revealed significant changes in several pathways associated with cell death and lung function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better define the mechanisms underlying the in vivo response to Magnéli phase exposure, lung tissue was collected 7 days post-exposure. Total RNA was isolated and processed for gene expression profiling using the SuperArray platform and IPA, as previously described (79). The gene expression profiling analysis revealed significant changes in several pathways associated with cell death and lung function.…”
Section: Resultsmentioning
confidence: 99%
“…Ingenuity Pathways Analysis (IPA) and the manufacturer's array software (Qiagen) was used to analyze gene expression data and conduct pathway analysis. IPA data were ranked and evaluated based on z -score as previously described by the research team (79).…”
Section: Methodsmentioning
confidence: 99%
“…Often, a gene's downstream targets may be validated by proteomics or transcriptomics. For example, the includes an article describing a mouse model for a rare allergic disease called eosinophilic esophagitis (EoE) whose phenotype strongly models the human disease (Eden et al, 2017). Mouse gene expression datasets were compared with those of humans with EoE, and confirmed by protein studies, demonstrating target validity, and revealing a new role for non-canonical NF-κB signalling in the disorder.…”
Section: Target Validitymentioning
confidence: 99%
“…The noncanonical NF-κB pathway has been recognized as a key regulator and promoter of the adaptive immune system, particularly in the development of secondary lymphoid organs. Prior studies from our group have demonstrated the role of this signaling pathway in mouse models of colon inflammation and eosinophilic esophagitis ( Allen et al, 2012 ; Eden et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%